Rumen fermentation pattern as affected by incorporation of high glucosinolate rapeseed-mustard (Brassica sp.) meal as a protein supplement in sheep - Tripathi, M K; Mishra, A S; Tyagi, A K; Karim, S A; Sharma, S D (The Indian Journal of Animal Sciences, 2012)
Rumen fistulated adult ewes (2) in switch-over design were fed 300g concentrate/day/head with ad lib. ground siris (Albezia lebbeck) pods and baru (Sorghum helipence) hay in 50:50 ratio. Basal 300 g concentrate provided 117 g mustard seed-meal (MSM) which was raised to 160, 200, 250, 300 and 350 g with the addition of pure MSM to study the effect of varying levels of MSM supplementation on rumen fermentation characteristics and thiocyanate (SCN) production. MSM as such contained 5.7% glucosinates. The pH of strained rumen liquor (SRL) ranged from 5.74 to 6.50, averaging 6.12 from 0 to 24 hr post feeding. There was no defined trend in pH changes, whereas, it was higher (P